Strategi peningkatan produktivitas dan ketahanan pangan petani sagu masyarakat Suku Mooy Kampung Aimas Distrik Aimas Kabupaten Sorong - Yahya F Wally; Rima HS Siburian; Hendri (Cassowary, 2023)
This study aims to determine the strategy of increasing productivity and food security of sago farmers in the local community of the Mooy Tribe, Aimas Village, Aimas District, Sorong Regency. Sampling of respondents was taken using a random system from sago farmers in the Mooy Tribe community in Aimas Village, Aimas District as many as 13 families. The data analysis used is quantitative data and qualitative data with the data sources used are primary data and secondary data. SWOT analysis was used to determine the strategy for increasing productivity of Mooy Tribe sago farmers. The results of the analysis show that the value of the SWOT analysis (+0.85 and -0.10) is in quadrant II with a diversification strategy. This shows that the income of sago farming by the Mooy Tribe community in Aimas Village, Aimas District, Sorong Regency is still in the feasible category and efforts are needed to introduce modern technology harvesting systems, high productivity cultivars, increase counseling and diversify processed sago products. Besides that, Mooy farmers still pay attention to sago-based food security of 20% of production and preserve conventional cultivation